2003
DOI: 10.1063/1.1544522
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of deterministic chaos in dyslipidemic erythrocytes under shear stress

Abstract: The erythrocytes deformation under shear stress, the viscoelastic properties and the effects observed on healthy donors and on dyslipidemic patients are investigated from the point of view of nonlinear dynamics. Finally it is suggested that the different results obtained could be useful with regard to pathophysiological disturbances and their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…The RBCs without treatment samples are more disordered (bigger entropy values) than the 2% glucose and also these ones are more disorder than the 5% glucose treatment. The dynamics for RBCs without treatment samples could correspond to fGn, results consistent with a previous study [12], while, the 2 and 5% glucose-incubated samples exhibit decreasing entropy values and increasing complexity values, that could correspond to short memory fBM; results consistent with our previous studies [6,23].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The RBCs without treatment samples are more disordered (bigger entropy values) than the 2% glucose and also these ones are more disorder than the 5% glucose treatment. The dynamics for RBCs without treatment samples could correspond to fGn, results consistent with a previous study [12], while, the 2 and 5% glucose-incubated samples exhibit decreasing entropy values and increasing complexity values, that could correspond to short memory fBM; results consistent with our previous studies [6,23].…”
Section: Resultssupporting
confidence: 92%
“…Our preliminary studies on red blood cells (RBCs) complex behaviour [5][6][7][8][9], have shown the competition between stochastic ordinal Brownian motion (oBm) and fractional Brownian motion (fBm), and make a crossover from one relaxation scenario when the erythrocytes are at rest to the other one, when the erythrocytes are subjected to shear stress. On this basis we applied a new concept in the study of the manifestation of this behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand that Costa et al and Chialvo argued that pathology/dysfunction is associated with less variability (lower entropy), which was consistent with our findings (Kaufman, 2007;Sung et al, 2005;Sung et al, 2007b). Nonlinear analysis has proved to be useful in the analysis of a variety of physiologic time series such as human heartbeats (Ivanov et al, 1999) and the shapes of red blood cells under flow stress (Korol & Rasia, 2003). Based on these empirical studies, it has been found that the time series from healthy subjects have higher entropy values than the time series from those with pathology/dysfunction.…”
Section: Reliability Of Surface Electromyography Analysissupporting
confidence: 80%
“…Regarding time series applications, biological time series are complex data that need to be distilled to useful information such as assessing an illness. Nonlinear analysis using fractal geometry and random walks theory proved to be useful in the analysis of a variety of time series such as correlations between global temperatures and solar activity (Scafetta & West, 2003), earthquake statistics (Scafetta & West, 2004), human heartbeat (Ivanov et al, 1999), and shapes of red cells under flow stress (Korol & Rasia, 2003). Recently, nonlinear time series generated by the back muscles' electrical activity was investigated between subjects with and without LBP motivated by the need to develop an evaluation tool for LBP (Lee et al, 2010;Sung et al, 2005;Sung et al, 2007a;Sung et al, 2010).…”
Section: Entropy Of Electromyographymentioning
confidence: 99%
“…Nonlinear analysis has proved to be useful in the analysis of a variety of physiologic time series such as human heartbeats (Ivanov et al, 1999) and the shapes of red blood cells under flow stress (Korol and Rasia, 2003). Based on these empirical studies, it was found that the time series from healthy subjects has higher entropy values than the time series from those with pathology.…”
Section: Median Frequencymentioning
confidence: 99%